Engineering the kinetics and interfacial energetics of Ni/Ni–Mo catalyzed amorphous silicon carbide photocathodes in alkaline media. Issue 18 (10th March 2016) - Digdaya, Ibadillah A.; Rodriguez, Paula Perez; Ma, Ming; Adhyaksa, Gede W. P.; Garnett, Erik C.; Smets, Arno H. M.; Smith, Wilson A.
Abstract : The photoelectrochemical performance of a-SiC photocathodes was enhanced by using a Ni/Ni-Mo dual-catalyst resulting in a significant increase of photocurrent density of −14 mA cm −2 at 0 V vs. RHE. Abstract : Photoelectrochemical (PEC) water splitting is a sustainable approach to produce a renewable fuel by harvesting the energy of the Sun to split water to form hydrogen and oxygen. In order to drive the water splitting reaction efficiently, substantial ohmic losses due to poor ionic conductivity of the electrolyte should be avoided, and therefore the reaction should be carried out at an extreme electrolyte pH. Herein we demonstrate the photoelectrochemical activity of an amorphous silicon carbide (a-SiC) photocathode for solar hydrogen evolution using an ultrathin nickel (Ni) film coupled with a nickel molybdenum catalyst (Ni–Mo) in a highly alkaline solution (pH 14). The incorporation of the Ni film coupled with Ni–Mo nanoparticles increases the number of active sites and therefore improves the kinetics of the hydrogen evolution reaction. Additionally, we report the influence of the catalyst configurations on the ohmic and solid liquid junction behavior on semiconducting interfacial layers. The a-SiC photocathode coated with the Ni/Ni–Mo dual-catalyst produces a photocurrent density of −14 mA cm −2 at 0 V vs. RHE using only cheap and abundant materials. This photocurrent is the highest recorded value from an amorphous-Si-based photocathode, and is achieved with a total film thickness of less than 150 nm.